Association of Increased Serum S100B Levels With High School Football Subconcussive Head Impacts - Zonner, Steven W.; Ejima, Keisuke; Bevilacqua, Zachary W.; Huibregtse, Megan E.; Charleston, Carmen; Fulgar, Ciara; Kawata, Keisuke (Frontiers in Neurology, 2019)
Astrocyte-enriched marker, S100B, shows promise for gauging the severity of acute brain trauma, and understanding subconcussive effects will advance its utility in tracking real-time acute brain damage. The aim of the study was to investigate whether serum S100B elevations were associated with frequency and magnitude of subconcussive head impacts in adolescents. This prospective cohort study of 17 high-school football players consisted of the following 12 time points: pre-season baseline, 5 in-season pre-post games, and post-season. A sensor-installed mouthguard recorded the number of head impacts, peak linear (PLA) and peak rotational (PRA) head accelerations from every practice and game. During the 5 games, players wore chest-strap heart-rate monitors to estimate players’ excess post-exercise oxygen consumption (EPOC), accounting for physical exertion effects. At each time point, blood samples were obtained and assessed for S100B and creatine kinase levels to account for astrocyte damage/activation and muscle damage, respectively. Using k-means clustering on the impact data, players were categorized into high- or low-impact group. Two players withdrew during the first month of the study. A total of 156 blood samples from 15 players were assessed for S100B and creatine kinase levels and included in the analysis. A median value of 596 head impacts from 15 players were recorded during all practices and games in a season. S100B levels were significantly elevated in all post-game measures compared with the respective pre-game values (median-increase, 0.022ug/L; interquartile-range, 0.011–0.043ug/L, p<0.05 for all games). Greater acute S100B increases were significantly associated with greater impact frequency, sum of PLA and PRA, with negligible contributions from physical exertion and muscle damage effects. The high-impact group exhibited greater increases in serum S100B levels at post-games than the low-impact group (high vs. low, 0.043+/-0.035ug/L vs. 0.019+/-0.017 ug/L, p=0.002). The degree of acute S100B increases was correlated with subconcussive head impact exposure, suggesting that acute astrocyte damage may be induced in an impact-dependent manner. Acute changes in serum S100B levels may become useful tool in monitoring real-time brain damage in sports.